2012
DOI: 10.5551/jat.13599
|View full text |Cite
|
Sign up to set email alerts
|

Does High-Sensitivity C-Reactive Protein or Low-Density Lipoprotein Cholesterol Show a Stronger Relationship with the Cardio-Ankle Vascular Index in Healthy Community Dwellers?: the KOBE Study

Abstract: Aim: High-sensitivity C-reactive protein (hs-CRP) identifies individuals at risk for cardiovascular disease (CVD) without an increased level of low-density lipoprotein cholesterol (LDL-C). The present study was performed to compare hs-CRP and LDL-C in association with the cardio-ankle vascular index (CAVI) in Japanese community dwellers considered to be at low risk for atherosclerosis from their level of traditional CVD risk factors. Methods: A community-based study involving 386 healthy Japanese (261 men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
0
28
1
1
Order By: Relevance
“…In our study population, however, no blood lipid parameters were associated with the ageadjusted CAVI ( Table 2). In concordance with these results, several studies have failed to detect a significant association between the CAVI and blood lipid levels [36][37][38] . Higashiyama et al 36) reported that the CAVI is more strongly correlated with the high-sensitivity C-reactive protein (hs-CRP) level than with the LDL cholesterol level.…”
Section: Resultsmentioning
confidence: 52%
“…In our study population, however, no blood lipid parameters were associated with the ageadjusted CAVI ( Table 2). In concordance with these results, several studies have failed to detect a significant association between the CAVI and blood lipid levels [36][37][38] . Higashiyama et al 36) reported that the CAVI is more strongly correlated with the high-sensitivity C-reactive protein (hs-CRP) level than with the LDL cholesterol level.…”
Section: Resultsmentioning
confidence: 52%
“…Measuring CRP has been recommended to identify patients at high risk for CHD in apparently healthy people with low LDL 3) . CRPisastrongerpredictorofatherosclerosisthanthe LDLlevel 14) andaddsprognosticinformationtothat conveyedbytheFraminghamriskscore;however,the associationbetweenCRPlevelsandamarkerofearly atherosclerosis, elevated carotid IMT, is not always consistent. In our study, we found that elevated carotidIMTandelevatedCRPinsubjectswithnormalLDLsharedsomecommondeterminants,suchas age, sex, BMI, serum triglycerides and HDL cholesterollevels.Aftercontrollingthevariableconfounding theelevatedIMT,CRPstillshowedasignificantassociation with elevated IMT.…”
Section: Characteristics Of the Participantsmentioning
confidence: 97%
“…Because healthy community dwellers rarely visit hospitals to receive health examinations for atherosclerosis, it is difficult to collect data about the parameters related to early-stage atherosclerosis in healthy individuals compared with unhealthy individuals. While health data obtained from work sites could contribute Our previous study 22) based upon the KOBE study showed that the hs-CRP level was positively associated with the CAVI, and the association between LDL-C and the CAVI was weak. These results indicated that the hs-CRP could be a more useful marker for atherosclerosis than LDL-C to detect early atherosclerosis in a healthy population without traditional risk factors for CVD, such as diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The KOBE participants had to meet the following criteria: 1) no current medication use for hypertension, diabetes mellitus or dyslipidaemia; and 2) no history of CVD or cancer. The details of the KOBE study were reported elsewhere 22) . Informed consent was obtained from each participant in writing.…”
Section: Introductionmentioning
confidence: 99%